The guerilla resistance in San Remegio, Antique during the Japanese occupation. - Pandoy, May Raymundo
This study is about the guerrila resistance in San Remigio Antique during the Japanese occupation. It aims to achieve the following objectives: 1.) To trace the origin and development of the guerilla resistance in San Remigio, Antique 2.) To describe the structural organization of the guerilla movement in San Remigio, Antique 3.) To ascertain the guerilla operations against the Japanese in San Remigio, Antique 4.) To describe the kind of life they had as guerillas 5.) To determine the significance of the guerilla resistance in San Remigio in relation to the Panay struggle for liberation from the Japanese., The researcher employed oral historical technique. Interviews were conducted with those survived guerilla members and civilians in San Remigio. The informants narrated their personal experiences during the war for liberation. The researcher also utilized library materials such as books, theses, journals and other written materials. The data collected were analyzed and cross-examined by verifying if the statements and testimonies of the interviewees corroborate with information gathered from library research in order to establish the credibility and authenticity of their accounts. From the informants the researcher found out that the Japanese were not able to build a strong foothold in San Remigio due to the initial resistance waged by the guerillas. The guerillas had greater geographical advantage, which enabled them to easily maneuver the enemy. Their familiarity of the terrain helped to be mobile. The kind of life as guerillas was certainty not easy. They lacked supplies such as arms and bullets, clothing, medicine and food. the success of the guerilla operations was also due to civilians who contribute food, intelligence and recruits.